The Influence of Service Quality and Trust on Repurchase Interest in Beauty Clinic Services - Yusria, Lana; Imronudin, Imronudin; Kuswati, Rini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
In the context of beauty clinic services in Surakarta's cosmetics industry, this study examines how service quality and brand image influence consumers' repurchase intentions, and how trust mediates this relationship. This study used a causal quantitative research methodology to investigate the connections between service quality, brand image, customer trust, customer satisfaction, and repurchase intention. The sample consists of 160 participants from Ella Beauty Clinic. Key variables are operationalized in this study, and data analysis is done using SmartPLS SEM (Partial Least Squares Structural Equation Modeling). The findings indicate that customer happiness does not have a direct impact on repurchase intentions, while customer trust has a considerable and favorable effect on repurchase intentions. Service quality has a beneficial effect on both customer happiness and trust, but it does not have a direct impact on repurchase intentions. On the other hand, the perception of a brand greatly impacts the level of satisfaction, trust, and likelihood of making future purchases. Furthermore, the trust serves as an intermediary between the quality of service and the perception of the brand, influencing the likelihood of repeat purchases. In contrast, customer satisfaction does not mediate these effects. This study enhances the comprehension of customer behavior in the cosmetics sector by providing practical insights for improving service quality and establishing consumer trust, which in turn promotes loyalty and repeat purchases. The results highlight the significance of brand image in influencing how consumers perceive and intend to engage with beauty clinics.